Microprocessors and Digital Systems - Alkhimov, Yu. V. Specialist in Non-Destructive Testing Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences 1958- (Tomsk Polytechnic University Publishing House, 2014)
The textbook is devoted to microprocessors, digital systems based on them and information processing in computing systems.The textbook has prepared at the TPU Department of Non Destructive Testing. It is intended for foreign students following the Master Degree Program in Electrical Engineering at Tomsk Polytechnic University.